2012
DOI: 10.1038/nature11333
|View full text |Cite
|
Sign up to set email alerts
|

Early-stage epigenetic modification during somatic cell reprogramming by Parp1 and Tet2

Abstract: Somatic cells can be reprogrammed into induced pluripotent stem cells (iPSCs) by using the pluripotency factors Oct4, Sox2, Klf4 and c-Myc (together referred to as OSKM)1. iPSC reprogramming erases somatic epigenetic signatures—as typified by DNA methylation or histone modification at silent pluripotency loci—and establishes alternative epigenetic marks of embryonic stem cells (ESCs)2. Here we describe an early and essential stage of somatic cell reprogramming, preceding the induction of transcription at endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
334
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(357 citation statements)
references
References 30 publications
17
334
0
6
Order By: Relevance
“…Our group and others have recently demonstrated that PARP1 is also involved in the efficient generation of iPSCs, which is probably due to PARP1‐dependent chromatin remodeling and epigenetic modulation 8, 11, 27. Here, we established strong physical and functional links between PARP1 and CHD1L and their roles in regulating the chromatin states of stemness genes.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our group and others have recently demonstrated that PARP1 is also involved in the efficient generation of iPSCs, which is probably due to PARP1‐dependent chromatin remodeling and epigenetic modulation 8, 11, 27. Here, we established strong physical and functional links between PARP1 and CHD1L and their roles in regulating the chromatin states of stemness genes.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, PARP1 occupies gene loci such as Nanog and Esrrb to enrich activation‐associated marker histone H3 lysine 4 dimethylation (H3K4me2) in early‐stage reprogramming 11, 30. In addition to our observation that PARP1 interacts with CHD1L, it is plausible that CHD1L may also coregulate the chromatin status of stemness genes, such as Pou5f1, Nanog , and Esrrb , through an interaction with PARP1.…”
Section: Resultsmentioning
confidence: 73%
“…Technological advances have allowed the mapping of diverse histone modifications in a large number of cell types (Doege et al, 2012, Ferguson et al, 2012, Shahhoseini et al, 2010. In this context a number of relevant DNA segments must be recognized, which will be discussed in more detail in the next paragraphs.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…2). In addition, Doege, et al (2012) recently reported that Parp1 and TeT2 serve essential roles in the regulation of epigenetic markers and the chromatin state at Nanog and Essrb during somatic cell reprogramming. Importantly, Parp1 induction further promotes Oct4 repro gramming factor binding to the pluripotency loci of Nanog and Essrb.…”
Section: C-myc Is a Direct Regulator Of Parp1 And Parylationmentioning
confidence: 99%
“…It was previously demonstrated that Parp1 is a regulator of Sox2 (Gao et al, 2009;Lai et al, 2012), and it is involved in the efficient generation of iPSCs (Lai et al, 2012). Recently, Doege et al (2012) reported that Parp1 and TeT2 contribute to early stage epigenetic modification during somatic cell reprogramming, and the induction of the Parp1 gene further promotes accessibility to the pluripotency factor Oct4. Therefore, it is conceivable that Parp1 and PARylation may be involved in the regulation of nuclear reprogramming or the maintenance of pluripotent properties in stem cells.…”
mentioning
confidence: 99%